Protection mechanisms against the challenges to journalists’ freedom of speech in Mexico, 2000-2022 - Pons Carrera, María Neus (2023)
This article argues that the application of state protection policies and mechanisms have not been sufficient to stop impunity, aggressions and murders of journalists in Mexico between 2000 and 2022. This paper reviews reports published by the organization Article 19 Mexico and Central America, Reporters without Borders, the Inter-American Commission on Human Rights and press articles; in addition, key actors answered questions from semi-structured interviews. The ineffectiveness of these policies and mechanisms is due, in part, to the confluence of state agents (armed forces, public officials) and non-state agents (political parties, organized crime) that exercise violence and aggression against journalists, which deepens the impunity and ineffectiveness of the policies. Mechanisms such as the “Hand in Hand” project, sponsored by the European Parliament, are a possibility to exercise international pressure jointly with civil society, although, at the moment, its scope is not quantifiable.